1992
DOI: 10.1161/01.cir.86.5.1536
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic subcutaneous or intramural administration of heparin on femoral artery restenosis after balloon angioplasty in hypercholesterolemic rabbits. A quantitative angiographic and histopathological study.

Abstract: Chronic subcutaneous heparin after balloon angioplasty results in a modest reduction in angiographic restenosis in this model; however, the absolute luminal diameter is not improved compared with before angioplasty, and plaque area and percent luminal narrowing by plaque were not different among the four treatment groups. Heparin can be delivered into an atherosclerotic plaque by a porous balloon, but this treatment does not reduce restenosis after angioplasty in this model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0
1

Year Published

1997
1997
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 31 publications
2
20
0
1
Order By: Relevance
“…The data presented indicated that LMW fucoidan reduced neointimal hyperplasia by Ϸ60% and increased the luminal area by Ϸ25%, making this compound one of the most efficient ever tested in experimental restenosis by using a noncontinuous administration regimen. 16 In contrast to heparin tested in animal models of balloon angioplasty 17,18 and clinical trials, 19 HMW fucoidan was already used at high dose (25 mg/kg in mice, 20 100 mg/kg in rats, 21 and 10 mg/kg per hour in rabbits 22 ) without bleeding. In the present study, the fraction of LMW fucoidan (8 kDa), used in rabbits at low dose (5 mg/kg), exhibited no anticoagulant activity in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The data presented indicated that LMW fucoidan reduced neointimal hyperplasia by Ϸ60% and increased the luminal area by Ϸ25%, making this compound one of the most efficient ever tested in experimental restenosis by using a noncontinuous administration regimen. 16 In contrast to heparin tested in animal models of balloon angioplasty 17,18 and clinical trials, 19 HMW fucoidan was already used at high dose (25 mg/kg in mice, 20 100 mg/kg in rats, 21 and 10 mg/kg per hour in rabbits 22 ) without bleeding. In the present study, the fraction of LMW fucoidan (8 kDa), used in rabbits at low dose (5 mg/kg), exhibited no anticoagulant activity in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…However, the rabbit model we used has been demonstrated to have several features in common with human atherosclerosis and to be reproducible. 28,29 The combination of initial balloon injury with high-cholesterol diet results in severe atherosclerotic lesions and very high cholesterol levels and is associated with a significant morbidity rate in the animals. This model produces lesions that resemble those in humans more closely than lesions produced by hypercholesterolemia alone.…”
Section: Discussionmentioning
confidence: 99%
“…26 %CSAN-P was calculated as the area bound by the internal elastic lamina minus luminal area times 100 divided by the area bound by the internal elastic lamina.…”
Section: Histomorphometrymentioning
confidence: 99%